Spice in the melting pot: The house on mango street, de Sandra Cisneros e How the García girls lost their accents, de Julia Alvarez - Maciel, Adriana Macedo Nadal (2007)
Chicano or Mexican-American and Dominican-American: people with latinity in their existence, a language, and the Hispanic origin in common, but with different backgrounds within the United States. The experience of living in the hyphen, the place where two worlds blend (or collide), is dramatized in texts written by authors who, from their own immigrant experiences, show the difficult journey from one culture to another and offer insights about accepting their Hispanic roots inside an environment which sees them as the Other. Sandra Cisneros, a Chicana author, and Julia Alvarez, a Dominican-American writer, make part of this movement which starts to verge on the literary canon and which, even though classified as Ethnic Literature, starts to find some room within North-American Literature. Through the comparison between Sandra Cisneros The house on Mango Street and Julia Alvarez How the García girls lost their accents, we attempt not only to trace a historic and socioeconomic panorama in which these books are inserted, but also to identify cultural phenomena and ideological aspects involved in this context. Because of the wide-ranging nature and for including areas of study which deal with the relationship between opposing forces, like dominator/dominated, as well as for the connection with post-colonial matters, some presuppositions of the Cultural Studies guide this work. In a semi-autobiographical manner, both authors depict the sorrow and conflicts of characters that search for acceptance and a dignifying space in this place-between, facing the barriers of sexism, racism, and social prejudice